Antioxidative, anti-androgenic, and inhibitory activities of ethanolic extract of Annona muricata leaf on sex hormones-induced benign prostate hyperplasia through in vivo and in silico studies - Ebenyi, Lilian N.; Chigozie, Victor U.; Destiny, Demian; Anyanwu, Chidinma (Natural Product Research, 2024)
Benign prostate hyperplasia (BPH) remains one of the major age-related urological problems in the world. Annona muricata (soursop) leaf has been reported to exhibit antiproliferative, antioxidant, and anti-inflammatory activities, among others, in the literature. Here, we aimed to unravel the antioxidative, antiandrogenic, and inhibitory activities of the ethanol extract of Annona muricata leaf (EEAML) on sex hormones-induced benign prostate hyperplasia (BPH) through in vivo and in silico studies. Thirty-six male rats were segmented into six groups of six animals each, the control group received water, and the BPH group and the remaining four groups were parentally infused with testosterone (T) and oestradiol (E2) (0.08 and 0.04 mg/Kgbwt) once daily for 28 days to induce BPH. After that, the control and BPH groups received water and normal saline, while the remaining four groups received finasteride (FIN) (0.1 mg/kgbwt) and EEAML (200, 400, and 800 mg/kgbwt) for another 28 days before sacrifice, and serum was collected for biochemical analysis. Additionally, the active ingredients of EEAML were identified using a Gas Chromatography Flame Ionisation Detector (GC-FID) followed by molecular docking (MD) against the human androgen receptor (hAR) target, and ADMET analysis of selected EEAML compounds was carried out. EEAML (200, 400, and 800 mg/kgbwt) restored the T and E2-induced depletion of reduced glutathione level, superoxide dismutase and catalase activities, and elevation of malondialdehyde, prostate-specific antigen, testosterone, and dihydrotestosterone levels in the serum of BPH rats. GC-FID analysis of EEAML showed the presence of 21 compounds from which 15 compounds were subjected to MD revealing that flavone, followed by ribalinidine, flavonone, anthocyanin, and naringenin displayed desirable binding affinities against the hAR target. ADMET analysis of these top-five EEAML compounds revealed that they were excellent oral bioavailable drug candidates with predicted minimal toxicities. In conclusion, EEAML exhibited antioxidative, antiandrogenic, and inhibitory activities owing to its phytoconstituents, which in turn could serve as drug templates for much better efficacy.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Annona muricata; anti-androgenic; antioxidative; benign prostate hyperplasia (BPH); ethanol extract of Annona muricata leaf (EEAML)